2019
DOI: 10.1002/oby.22640
|View full text |Cite
|
Sign up to set email alerts
|

Association of Food Access, Recreational Opportunities, and Natural Amenities with Engagement in the Veterans MOVE! Weight Management Program

Abstract: Objective The aim of this study was to examine the association of county‐level food access, recreational opportunities, and natural amenities with participant engagement in a weight management program. Methods In this cohort study, participants in the Veterans Health Administration MOVE! weight management program between October 1, 2007, and September 30, 2013, were observed for 12 months after enrollment. Engagement was measured as the number of program visits per year at 12 months. Cross‐sectional analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…1 Social and structural determinants of health and social injusticies that contribute to obesity disparities the results of a study using data from the Behavioral Risk Factor Surveillance System showed that regardless of race and ethnicity, residents of low-income communities with food and physical activity deserts have higher BMI levels than residents of high income communities that have access to active commuting and fewer unhealthy food outlets [31]. In addition, Graham et al [32] found that veterans living in counties with fewer farmer's markets and natural amenities were less likely to be engaged in the Veterans Health Administration MOVE! Program.…”
Section: Social Inequities and Social Injustices That Contribute To D...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Social and structural determinants of health and social injusticies that contribute to obesity disparities the results of a study using data from the Behavioral Risk Factor Surveillance System showed that regardless of race and ethnicity, residents of low-income communities with food and physical activity deserts have higher BMI levels than residents of high income communities that have access to active commuting and fewer unhealthy food outlets [31]. In addition, Graham et al [32] found that veterans living in counties with fewer farmer's markets and natural amenities were less likely to be engaged in the Veterans Health Administration MOVE! Program.…”
Section: Social Inequities and Social Injustices That Contribute To D...mentioning
confidence: 99%
“…Added sugar intake, including sugar-sweetened beverage (SSB), is associated with a greater risk of incident obesity among young adults [32]. Racial and ethnic minorities and individuals with low incomes have significantly higher Community-level intervention focused on increasing accessing to affordably priced fruits and vegetable in rural communities [74] Expanded acceptance of nutrition benefits programs Increase the number of farmer's markets that accept nutrition benefits programs…”
Section: Federal State Local and Institutional Policiesmentioning
confidence: 99%
“…In yet another study of veterans, Graham et al (7), showed that greater engagement in the Veterans Health Administration's MOVE! weight management program was associated with older age, female sex, white race, being married, and being retired.…”
Section: Obesitymentioning
confidence: 99%
“…Graham et al(7) A cross-sectional analysis of the number of visits per person (outcome measure) at 12 months after Veterans Health Administration MOVE! program enrollment was conducted to examine the distribution and relationships between participant demographics, program attributes, and county-level characteristics.…”
mentioning
confidence: 99%